2010
DOI: 10.1063/1.3507873
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation dynamics of ionic argon pentamer

Abstract: Photodissociation of the ionized argon pentamer, Ar + 5 , is studied using an extended diatomicsin-molecules interaction model with the inclusion of the spin-orbit coupling and various dynamical approaches. A thorough comparison with the experimental data available in the literature is presented, including photofragment abundances and their kinetic and internal energy distributions.New predictions are reported for ultra-violet photoexcitation energies, a range that has not been studied before either experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…We note here that our work on Ar N + is the first experimental report on the structures of Ar clusters. The dissociative nature of the cluster 89,100–102 and the lack of high resolution spectral features 82,84,89 make ED perhaps the only choice in this case.…”
Section: Discussionmentioning
confidence: 99%
“…We note here that our work on Ar N + is the first experimental report on the structures of Ar clusters. The dissociative nature of the cluster 89,100–102 and the lack of high resolution spectral features 82,84,89 make ED perhaps the only choice in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Note also that alternative names like hemiquantal method [14,16,22,23,24,25,26,27] and semiclassical method [19,28,29,20,30,21,31] were also used in our previous studies.…”
Section: Dynamicsmentioning
confidence: 99%
“…In the specific case of rare-gas cluster cations, it means that partial charges may be produced on separate fragments. Nevertheless, previous simulations on small rare-gas cluster cations [27][28][29]38 have clearly shown that realistic predictions can be obtained even if a purely mean-field method is employed provided heavily averaged quantities are considered (fragments abundance, mean kinetic energy released, etc.) and if partial charges are properly treated as quantum probabilities that the positive charge resides on a particular fragment.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…A lot of experiments were performed at that time focusing on their photoabsorption spectrum over a broad range of photon energies and cluster sizes [2][3][4] as well as subsequent, post-absorption dynamics. 2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Up to now, however, calculations on the rare-gas cluster cation photodynamics have not exceeded the smallest cluster sizes [19][20][21][22][23][24][25][26][27][28][29] or very short simulation times. 30,31 As a consequence, most of the experimental photodissociation data obtained for Ar N + clusters have still been waiting for their appropriate theoretical interpretation even though simple and computationally cheap interaction models based on the diatomics-in-molecules approach (DIM) 32 exist for Ar N +33 (and also for other rare gases 1,33 ) for quite a long time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation